Social development and Philippine Overseas Employment policy (1975-1997) issues, problems and prospects - Tigno, Jorge V.; Rye, Ranjit Singh; Macabiog, Teofino (2000)
It is significant to note that under the three political administrations examined in this article, overseas employment has been frequently touted as one that contains a strong development potential. Migration is oftentimes perceived by politicians and public alike as the offshoot of the failure of existing social development programs and strategies at the national level such as creating viable domestic employment and internally generating economic and capital resources. This article attempts to show how policies relating to overseas employment promotion and development have affected the country's social development concerns and outlook. Also, it proposes certain operational parameters by which overseas labor migration policies and phenomena may be assessed especially as regards the more relevant concerns for social development. More specifically, it seeks to: (1) describe the nature and nuances of the national policy program on overseas employment of the Philippines covering three successive presidencies (i.e. from the mid-1970s to the late 1990s); (2) assess the social development impacts and implications of the program especially in relation to Filipino migrant workers and their families; and (3) enumerate some of the persistent as well as likely social development issues and problems that arise from the conduct of the policy and program.
Keywords: Filipino foreign workers; Overseas migration; Labor migration; Migration policy; Filipino foreign workers -- Employment